2019
DOI: 10.1590/1982-0224-20190118
|View full text |Cite
|
Sign up to set email alerts
|

Upstream dam impacts on gilded catfish Brachyplatystoma rousseauxii (Siluriformes: Pimelodidae) in the Bolivian Amazon

Abstract: This paper explores the effects of two run-of-river dams (Jirau and Santo Antônio) built in cascade in the middle Madeira River (Brazil) on the interruption of long-distance migration routes of the gilded catfish (Brachyplatystoma rousseauxii). A participative monitoring system was set up to compare capture by commercial fishers approximately 1500 km upstream of the dams in Bolivia, before (1998-2007) and after (2015-2017) dam closure. A significant decrease in gilded catfish catches and in catch per unit effo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 35 publications
0
23
0
3
Order By: Relevance
“…Mean length of Dourada increased systematically upstream, with a corresponding increase in estimated SPR. This is assumed to reflect ontogenetic migration of large fish, although Van Damme et al (2019) suggested an influence of diminished upstream migration of small individuals due to dams. One solution to such spatial heterogeneity in size structure may be to calculate an average SPR from a fish sample collected throughout the river, to ensure a representative population size distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Mean length of Dourada increased systematically upstream, with a corresponding increase in estimated SPR. This is assumed to reflect ontogenetic migration of large fish, although Van Damme et al (2019) suggested an influence of diminished upstream migration of small individuals due to dams. One solution to such spatial heterogeneity in size structure may be to calculate an average SPR from a fish sample collected throughout the river, to ensure a representative population size distribution.…”
Section: Discussionmentioning
confidence: 99%
“…For long‐distance migrants, such as goliath catfishes and other longitudinal migrants, any dam on their migration routes will interfere by isolating their breeding areas from feeding and nursery areas (Agostinho, Pelicice, & Gomes, 2008; Ribeiro et al, 1995), depleting resident populations above the dams, with unlikely long‐term chances of persistence (e.g. for B. rousseauxii in the Madeira; Hauser, 2018; Van Damme et al, 2019). Large catfish fisheries usually decline upstream and downstream of dams, as was observed above the Tucuruí dam on the Tocantins River (Ribeiro & Petrere, 1988; Ribeiro et al, 1995).…”
Section: Threats To Migratory Species In the Amazon Basinmentioning
confidence: 99%
“…Currently, one of the main problems for the sustainability of large migratory catfish fisheries in the Amazon basin is the construction and operation of hydroelectric dams along the main channels of its largest tributaries, restricting the reproductive and trophic migrations of fish species that live in or utilize the flood basin's aquatic environments as a migratory route (Gubiani et al, 2011;Winemiller et al, 2016). Recent records indicate a decrease in the amount of fish able to cross these barrages (Hauser et al, 2019), which is reflected in the decrease seen in records of fish production reported in the fishery landing sites, especially in upstream regions of these enterprises (Damme et al, 2019). This has been a direct source of harm to small-scale fisheries, which are traditionally responsible for maintaining the supply of animal protein in the riverine communities of the study area (Fearnside, 2013;Lima et al, 2017;Santos et al, 2018).…”
Section: Discussionmentioning
confidence: 99%